Relationship between molar incisor hypomineralization and dental caries at eight-year-old children - Marković Đurić Ljiljana; Dolić Olivera; Obradović Marija; Tošić Mirjana; Ernaut Maja (Serbian Medical Society - Dental Section, Belgrade, 2017)
Introduction The aim of the present study was to determine the relationship between Molar Incisor Hypomineralization (MIH) and caries in school children from Banja Luka region, Republic of Srpska. Materials and methods One calibrated dentist evaluated a sample of 529 schoolchildren, eight years old, according to the European Academy of Pediatric Dentistry (EAPD) criteria on MIH presence. Dental caries was assessed using the DMFT (Decayed, Missing, Filled Teeth) criteria. Results DMFT/dmft was significantly higher in children with MIH than without MIH (p < 0.001). In the MIH group of children, high values of caries indices (%DMFT/%dmft and mean DMFT/dmft) were found. Conclusion Significant association between MIH and dental caries in eight-year-olds was found.